Application of geochemical, mineralogical and geotechnical methods to site characterization for road construction purposes at a1 highway northeastern Algeria - Viatcheslav Yakovitch, Savenko; Dahoua, Lamri; Hadji, Riheb; Zahri, Farid; Ossitchenko, Elina (International Journal of Engineering and Technology, 2018)
This research study focused on the role of the lithological, physical–mechanical and structural factors in the slope movements’ genesis using a combination of methods. The geochemical, mineralogical and geotechnical characteristics of the study area soils were identified by various tests and analyzes such as X-ray diffractometry, X-ray fluoricence, infrared spectroscopy, particle size distribution and Atterberg Limit. This study was carried out through the comprehensive compilation of the analyzes results to qualitatively assess the tendency of the study area geological formations to sliding wich are commonly composed of fine-grained soils. Quantitative and qualitative clay contain of the soils were examined in relation on 12 historical landslides. It was found that laboratory determined instabilities of the basement materials from the slip zones was closely related to clay content, liquid limit and plasticity index. This study has allowed to improve the understanding of the genesis of mass wastiong under the study site.